Lipopolysaccharide Causes an Increase in Intestinal Tight Junction Permeability in Vitro and in Vivo by Inducing Enterocyte Membrane Expression and Localization of TLR-4 and CD14 - Guo, Shuhong (American Society for Investigative Pathology, 2013)
Bacterial-derived lipopolysaccharides (LPS) play an essential role in the inflammatory process of inflammatory bowel disease. A defective intestinal tight junction (TJ) barrier is an important pathogenic factor of inflammatory bowel disease and other inflammatory conditions of the gut. Despite its importance in mediating intestinal inflammation, the physiological effects of LPS on the intestinal epithelial barrier remain unclear. The major aims of this study were to determine the effects of physiologically relevant concentrations of LPS (0 to 1 ng/mL) on intestinal barrier function using an in vitro (filter-grown Caco-2 monolayers) and an in vivo (mouse intestinal perfusion) intestinal epithelial model system. LPS, at physiologically relevant concentrations (0 to 1 ng/mL), in the basolateral compartment produced a time-dependent increase in Caco-2 TJ permeability without inducing cell death. Intraperitoneal injection of LPS (0.1 mg/kg), leading to clinically relevant plasma concentrations, also caused a time-dependent increase in intestinal permeability in vivo. The LPS-induced increase in intestinal TJ permeability was mediated by an increase in enterocyte membrane TLR-4 expression and a TLR-4–dependent increase in membrane colocalization of membrane-associated protein CD14. In conclusion, these studies show for the first time that LPS causes an increase in intestinal permeability via an intracellular mechanism involving TLR-4–dependent up-regulation of CD14 membrane expression.